PEMANFAATAN MESIN STIRLING SEBAGAI SUMBER ENERGI ALTERNATIF UNTUK SISTEM PENCATU DAYA SKALA KECIL: Pemanfaatan Mesin Stirling Sebagai Sumber Energi Alternatif Untuk Sistem Pencatu Daya Skala Kecil - Muhammad Rizky (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2025)
Limited access to electricity in remote areas is a serious challenge in national energy distribution. This study aims to examine the use of Stirling engines as an environmentally friendly alternative energy source that can be used for small-scale power supply systems. Stirling engines were chosen because of their ability to convert heat energy from various sources into mechanical energy, which is then converted into electrical energy. The research methods include prototype design, performance testing, and interviews with experts in the field of energy conversion. The test results show that Stirling engines are capable of producing an average electrical power of 5.7 watts at an operating temperature of ? 300°C, with an energy conversion efficiency of around 15–20%. The integration of a microcontroller-based power control system has succeeded in increasing output stability and facilitating system performance monitoring. The interview results support that this technology has the potential to be further developed in areas that have not been reached by electricity. This study concludes that Stirling engines are an alternative solution that is applicable, economical, and supports the development of renewable energy in Indonesia.